Past and Current Perspectives in Modeling Bacteria and Blood–Brain Barrier Interactions - Kim, Brandon J.; Shusta, Eric V.; Doran, Kelly S. (Frontiers in Microbiology, 2019)
The central nervous system (CNS) barriers are highly specialized cellular barriers that promote brain homeostasis while restricting pathogen and toxin entry. The primary cellular constituent regulating pathogen entry in most of these brain barriers is the brain endothelial cell (BEC) that exhibits properties that allow for tight regulation of CNS entry. Bacterial meningoencephalitis is a serious infection of the CNS and occurs when bacteria can cross specialized brain barriers and cause inflammation. Models have been developed to understand the bacterial – BEC interaction that lead to pathogen crossing into the CNS, however, these have been met with challenges due to these highly specialized BEC phenotypes. This perspective provides a brief overview and outlook of the in vivo and in vitro models currently being used to study bacterial brain penetration, and opinion on improved models for the future.